Predictive Role of Fluorescein Angiography in Retinopathy of Prematurity - Gianluca Dini; Alfredo Beccasio; Francesco Della Lena; Alberto Verrotti; Carlo Cagini (MDPI AG, 2024)
Background: Fluorescein angiography (FA) has been a pivotal tool for studying the pathophysiology of retinopathy of prematurity (ROP) in vivo. We examined the course of ROP using FA to assess the predictive value of angiographic features. Methods: This is an observational retrospective cohort study of eyes screened for ROP with a binocular indirect ophthalmoscope and FA. RetCam fundus imaging and video digital fluorescein angiography were performed in the neonatal intensive care unit of Santa Maria Hospital of Perugia. The masked grading of the FA images was retrospectively conducted by two ROP expert ophthalmologists. Results: A total of 80 eyes of 40 patients were included for this study. Among the angiographic features evaluated, leakage, shunts, and tangles were predictive of the development of treatment-requiring ROP (p < 0.05). Conclusions: FA can add to our understanding of the evolution of vascular abnormalities in the course of ROP and can help predict which eyes will go on to treatment.